The impact of carbon coating on the synthesis and properties of α′′-Fe16N2 powders. Issue 18 (25th April 2016) - Bridges, C. A.; Rios, O.; Allard, L. F.; Meyer, H. M.; Huq, A.; Jiang, Y.; Wang, J.-P.; Brady, M. P.
Abstract : It is demonstrated that a carbon coating on the precursor Fe nanoparticles can improve the yield of α′′-Fe16 N2 by reducing the level of sintering experienced by precursor particles during ammonolysis, and that resulting α′′-Fe16 N2 particles can exhibit relatively high saturation magnetization and coercivity. Abstract : This paper presents the preparation of carbon composite Fe16 N2 powders, and the influence of a protective carbon coating on the yield and magnetic properties of Fe16 N2 . Nanoparticle precursors with and without carbon were reacted under ammonia gas flow to produce Fe16 N2 . Neutron and X-ray powder diffraction indicate that the powders contain typically 40–60% Fe16 N2, with the remaining phases being unreacted iron, Fe4 N or Fe3 N. Transmission electron microscopy demonstrates that the carbon coating is effective at reducing the level of sintering of Fe nanoparticles during the reduction stage prior to ammonolysis. XPS results support the retention of a carbon coating on the surface after ammonolysis, and that there is Fe–C bonding present at the particle surface. In situ TEM was used to observe loss of ordering in the nitrogen sublattice of carbon composite Fe16 N2 powders in the range of 168 °C to 200 °C. Magnetic susceptibility measurements show maximum values for saturation magnetization in the range of 232 emu g −1, and for coercivity near 930 Oe, for different samples measured up to 2 T applied field at 300 K.